Design principles for research & development performance measurement systems: a systematic literature review - Oliveira, Andre Ribeiro de; Proença, Adriano (Brazilian Journal of Operations & Production Management, 2019)
Goal: This paper aims to set the foundation on which a performance measurement system for the R&D function will be developed, assuming it not only as an organizational division, but also as a comprehensive process in order to better evaluate its efficiency and effectiveness. Design/Methodology/Approach: This paper adopts a Design Science Research strategy as its methodological basis. It focuses on bringing guidelines from the body of organizational theory of knowledge to design effective management solutions for an R&D performance measurement system. Results: A set of well-defined Design Principles to guide performance measurement system designs for R&D management. Limitations of the investigation: Even though the design principles have been systematically obtained from the literature review, there was no adequacy test of these principles in practical cases, which should be conducted in future research. Practical Implications: Managers and leaders of R&D teams may use theory-grounded guidelines to design their performance systems and to adjust such systems to their specific needs. Originality/ Value: The main practical contribution of the study findings is to provide a comprehensive set of guidelines to design a R&D Performance Measurement System, rather than proposing another new complete theoretical framework to add to the literature.